How to implement shareholder democracy - Oliver D. Hart; Hélène Landemore; Luigi Zingales (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2024)
We propose a novel way to give mutual funds' investors a voice, an alternative to the pass-through voting large mutual funds companies are starting to implement. Based on the experience of citizen assemblies in the political sphere, we propose allocating the power to decide how to cast mutual funds' votes in corporate ballots on environmental, social, and political issues to a randomly drawn assembly of its investors. We analyze the advantages and limitations of such a model and discuss various implementation issues.
Keywords: 330